Bentuk Bawang Merah Sebagai Motif Hias Cardigan Wanita - Vonia, Lahara Tasya; Bahrudin, Ahmad; Hendra, Hendra (Relief : Journal of Craft, 2024)
Shallots are a plant that provides many benefits to humans, one of which is that shallots can be used as a cooking spice and traditional medicine. Shallots have a unique shape, in terms of structure they have various shapes, some are round, sometimes a bit oval, which makes the creator interested in making the visual of the shallot plant as a motif on women's cardigans. The shape of the shallot plant is made into a batik motif which is created using written batik techniques and sewing techniques, while the material used to make the work is silk cotton. The resulting work consists of 7 works, with the titles composition, symmetrical, balance 1, balance 2, sowing, side by side, growing and developing